807C/T polymorphism of platelet glycoprotein Ia gene is associated with cerebral hemorrhage in a Chinese population. (2nd August 2016) - Zeng, Yi; Zhang, Le; Hu, Zhiping; Yang, Qidong; Ma, Mingming; Liu, Baoqiong; Xia, Jian; Xu, Hongwei; Liu, Yunhai; Du, Xiaoping
Abstract : Platelet glycoprotein (GP) mediated the role of platelet in coagulation. Platelet GP Ia 807C/T is the only GP polymorphism associated with the expression levels of GP Ia/IIa (the platelet collagen receptor). Recently, the GP Ia 807C/T polymorphism has been reported to have no association with cerebral hemorrhage (CH) in two studies pertained to Caucasian populations. The purpose of this study is to evaluate the association between platelet GP Ia 807C/T polymorphism and CH in a Han Chinese population. We performed genotype analysis for platelet GP Ia 807C/T polymorphism in a case-control study involving 195 patients with CH and 116 age- and sex-matched controls. In contrast to previous reports, we found that the frequencies of GP Ia 807C/T T allele, CT and TT genotype were much higher in CH patients than in controls (33.9% vs. 22.8%, p = 0.004; 45.5% and 11.1% vs. 40.4% and 2.6%, p = 0.022). Logistic regression analysis revealed that the presence of GP Ia 807C/T C allele and CC genotype were both associated with a decreased risk of CH compared with T allele, CT and TT genotypes, respectively (adjusted odds ratio [OR] = 0.565, 95% CI: 0.384–0.887, p = 0.005; adjusted OR = 0.172, 95% CI: 0.043–0.639, p = 0.009; adjusted OR = 0.254, 95% CI: 0.085–0.961, p = 0.041, respectively). These findings indicated that platelet GP Ia 807C/T polymorphism could be a protective factor of CH in the Chinese population.